Toward a criminology of terrorism - LaFree, Gary (Cambridge elements Elements in criminology)
The study of terrorism represents one of the major turning points in criminology of the twenty-first century. In the space of just two decades, research on terrorism and political extremism went from a relatively uncommon niche to a widely recognized criminological specialization. Terrorism research now appears in nearly all mainstream criminology journals; college courses on terrorism and political violence have been added to the curricula of most criminology departments; and a growing number of criminology students are choosing terrorism as a suitable topic for class papers, research topics, theses and dissertations. The purpose of this book is to explore similarities and differences between terrorism and more ordinary forms of crime. This Element considers the ways that criminology has contributed to the study of terrorism and the impact the increasing interest in terrorism has had on criminology. This Element also provides empirical comparisons of terrorist attacks to more ordinary crimes and criminal offenders. This title is also available as Open Access on Cambridge Core.